2011
DOI: 10.1007/s12598-011-0319-0
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization and its influence on microstructures and mechanical properties of laser solid formed nickel base superalloy Inconel 718

Abstract: Recrystallization, which is often occurred in heat treated deformed materials, was examined in laser solid formed (LSFed) Inconel 718 alloy. Its influence on microstructures and mechanical properties of LSFed Inconel 718 alloy were investigated. Microstructure observation indicated that as-LSFed grains were refined and columnar grains were substituted by recrystallized equiaxed grains after recrystallization. The grain refinement mechanism was analyzed and three recrystallized grain nucleation models were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Owing to the locally concentrated energy input, repeated rapid heating, fast solidification rate, and consequent plastic deformation, residual stress remained during the SLM process [ 19 ], which could be the driving force for the normal grain growth. The grain boundaries with high surface energy serve as the favored locations for grain growth [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the locally concentrated energy input, repeated rapid heating, fast solidification rate, and consequent plastic deformation, residual stress remained during the SLM process [ 19 ], which could be the driving force for the normal grain growth. The grain boundaries with high surface energy serve as the favored locations for grain growth [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, treatment at 1100 °C rather than 980 °C has been suggested to achieve sufficient delta dissolution for traditionally processed Alloy718 [ 18 ]. Moreover, solutions treated at 1100 °C have sufficient energy at the beginning of grain growth, which is associated with a release of the stored strain energy through the annihilation of dislocations [ 19 ]. Further, coarsening of the grain structure was observed with heating above 1100 °C in a laser-solid-formed superalloy.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Figure 13 illustrates the different microstructural features that were observed after 1 h holding at 1100 • C. Specifically, FEG-SEM examination showed that columnar grain structure has been altered and converted to a mixture of columnar and equiaxed grains as indicated in Figure 13a. Other complex grain geometries may result from grain boundary migration or sub-grain coalescence [35]. It is also worth noting that, the residual columnar grains became shorter after homogenization treatment and the grain size of the equiaxed structure is in the 30 to 50 µm (equivalent circle diameter) range.…”
Section: Microstructure Evolution In Homogenized and Hip-treated Specmentioning
confidence: 99%
“…The heat-treated material generally shows isotropic mechanical behaviour. This is the result of the transformation of the columnar dendritic microstructure, formed during the DED process into an equiaxed microstructure thanks to the recrystallisation phenomenon [17]. Additionally, the combined effects of the precipitation hardening and the stress relief improve the material properties.…”
Section: Introductionmentioning
confidence: 99%